1980
DOI: 10.1099/00221287-118-2-329
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition and Chemotaxonomy of Pseudomonas putrefaciens (Alteromonas putrefaciens)

Abstract: The major polar lipids in cells of Pseudomonas putrefaciens NCIB 10472 grown on nutrient agar were phosphatidylethanolamine, phosphatidylglycerol, a glucosyldiacylglycerol, a glucuronosyldiacylglycerol and an ornithine amide lipid. An additional phospholipid, tentatively identified as acyl phosphatidylglycerol or bis-phosphatidic acid, was a trace component of the wall lipids from broth cultures, which lacked the glycolipids and the ornithine amide lipid. The wall lipids from broth cultures of three further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…In the present study, exogenous desaturase cofactors were added to a viable culture and the effect on cellular PUFA levels monitored. Addition of desaturase cofactors to the standard medium increased the total percentage of PUFA (Wilkinson & Caudwell, 1980;Moule & Wilkinson, 1987). This in itself, however, may not be surprising.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, exogenous desaturase cofactors were added to a viable culture and the effect on cellular PUFA levels monitored. Addition of desaturase cofactors to the standard medium increased the total percentage of PUFA (Wilkinson & Caudwell, 1980;Moule & Wilkinson, 1987). This in itself, however, may not be surprising.…”
Section: Discussionmentioning
confidence: 91%
“…This in itself, however, may not be surprising. Wilkinson & Caudwell (1980) did not determine the double bond position of monounsaturated fatty acids, and would therefore not have been able to identify any trans-fatty acids present. Moule & Wilkinson (1987) did identify double bond position by mass spectral analysis of picolinyl ester derivatives (Wait & Hudson, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…), was used for descending chromatography. Electrophoresis was carried out with pyridine/acetic acid buffers of pH 3.6 or 5.3 (Wilkinson & Caudwell, 1980). Spots were detected by using ninhydrin, the HaneslIsherwood reagent for phosphates, or the periodate/Schiff reagents for 1,2-diols (Cox & Wilkinson, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids 15 : 0 iso and 13 : 0 iso were characteristic of the two Shewanella strains (CCUG 13452 and CCUG 39064) with levels of 12n2 and 7n8% (S. putrefaciens) and 26n8 and 5n9% (S. algae). Several studies have identified 15 : 0 iso and 13 : 0 iso as characteristic fatty acids of Shewanella (formerly some Pseudomonas) species (Wilkinson & Caudwell, 1980 ;Nichols et al, 1992 ;Khashe & Janda, 1998) and the lack of these fatty acids clearly places strain CCUG 30811 T in a different group. Likewise, fatty acid 18 : 1 cis11\ trans9\trans6 accounted for 7n2 % of the fatty acids in strain CCUG 30811 T , but was only detected at a level of 1n4-1n8 % in the Shewanella species.…”
Section: Cellular Fatty Acid Profilesmentioning
confidence: 99%